Redefining Village Power: Asymmetric Autonomy and Governance Innovation in the Digital Age - Sukarno, Sukarno (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study explores the reconstruction of village government authority within the framework of asymmetric autonomy in the digital era, guided by the theoretical framework of good governance. Utilizing a juridical-normative approach, the research examines key legal sources—particularly Law No. 6 of 2014 on Villages (UU Desa)—as well as academic literature on decentralization and village autonomy. The findings show that village autonomy is an inherent right, rooted in hak asal-usul (origin-based rights), and recognized by the Indonesian Constitution. However, its implementation faces significant challenges, including disparities in capacity among regions, regulatory overlaps, and weak accountability mechanisms—especially in underdeveloped villages. The digitalization of village governance offers potential to strengthen transparency, administrative efficiency, and community participation. The study proposes that reconstruction of village authority should adopt an asymmetric autonomy model, tailored to local conditions while upholding the principles of good governance: transparency, accountability, participation, effectiveness, rule of law, and responsiveness.Key recommendations include strengthening the legal recognition of traditional village rights, localizing and simplifying regulations, improving digital literacy and infrastructure at the village level, and fostering participatory oversight. These steps aim to realize village autonomy that is context-sensitive, equitable, and aligned with a democratic and responsive state structure.